Thulium-doped optical fiber and preparation method thereof
By using the core layer of germanium aluminum thulium co-doped silicate material and the transitional step layer of germanium silicate material in the thulium doped fiber, combined with the preparation method of MCVD and solution doping, the problem of low efficiency of thulium doped fiber is solved, and the effect of high efficiency and single-mode output is achieved.
Patent Information
- Application Number
- CN202510148521.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fiber efficiency of existing thulsh-doped fibers is low, and the thulsh ion quantum loss leads to high heat yield, affecting its application efficiency.
The thulsh-doped optical fiber design is adopted including a core layer, a transition step layer, a barrier layer, a cladding layer and a coating layer. The core layer is composed of a germanium aluminum thulsh co-doped silicate material, the transition step layer is a germanium silicate material, and the barrier layer is a fluorosilicate material, and is prepared by MCVD and solution doping method.
The fiber efficiency of the thulsh-doped fiber is improved, the phonon energy and numerical aperture of the core layer are reduced, the cross relaxation probability between the thulsh ions is enhanced, and the laser single-mode output is promoted.
Smart Images

Figure CN119661071A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of optical fiber technology, and in particular to a thulium-doped optical fiber and a preparation method thereof. Background Art
[0002] 2μm lasers are widely used in biomedicine, plastic processing, atmospheric transmission, gas sensing, nonlinear optics, and military applications. High-frequency, high-energy-density 2μm lasers can be used to measure atmospheric pollutants in the air. In addition, the absorption coefficient of water in human tissue for 2μm lasers is as high as 600cm -1 The use of 2μm laser can better control the penetration depth of laser into biological tissue and achieve good surgical hemostasis effect.
[0003] Currently, the rare earth ions used for 2μm band laser output are mainly Tm 3+ Ions (thulium), for thulium-doped optical fibers, due to the unique cross-relaxation effect between thulium ions, thulium-doped optical fibers have high requirements on doping concentration, and high concentration doping corresponds to high absorption coefficient. At the same time, the high quantum loss of thulium ions also leads to high heat generation, which poses a great challenge to the efficiency of thulium-doped optical fibers and the application of thulium-doped lasers. Therefore, it is of great significance to study methods to improve the efficiency of thulium-doped optical fibers.
[0004] Therefore, there is an urgent need for a thulium-doped optical fiber and a preparation method thereof to solve the above technical problems. Summary of the invention
[0005] The object of the present invention is to provide a thulium-doped optical fiber and a preparation method thereof, so as to improve the technical problem of low optical fiber efficiency of the thulium-doped optical fiber in the prior art.
[0006] In order to solve the above technical problems, the present invention first provides a thulium-doped optical fiber, comprising a core layer, a transition step layer, a barrier layer, a cladding layer and a coating layer arranged in sequence from the inside to the outside along the radial direction, wherein the refractive index of the transition step layer is greater than the refractive index of the cladding layer and less than the refractive index of the core layer; The core layer comprises germanium-aluminum-thulium co-doped silicate material, the transition step layer comprises germanium silicate material, and the barrier layer comprises fluorosilicate material.
[0007] Accordingly, the present invention also provides a method for preparing the above thulium-doped optical fiber, the method comprising: S10, introducing a first mixed gas into a quartz tube to deposit a barrier layer on the inner wall of the quartz tube to obtain a first reaction tube, wherein the first mixed gas includes a mixed gas of oxygen, silicon tetrachloride and sulfur hexafluoride; S20, introducing a second mixed gas into the first reaction tube to deposit a transition step layer on the inner wall of the first reaction tube to obtain a second reaction tube, wherein the second mixed gas includes a mixed gas of oxygen, silicon tetrachloride and germanium tetrachloride; S30, introducing a third mixed gas into the second reaction tube to deposit a loose layer on the inner wall of the second reaction tube to obtain a third reaction tube, wherein the third mixed gas includes a mixed gas of oxygen, helium, silicon tetrachloride and germanium tetrachloride; S40, immerse the third reaction tube in a solution containing Tm 3+ and Al 3+ in ionic solution; S50, baking the third reaction tube under a fourth mixed gas to obtain a dry reaction tube, the fourth mixed gas comprising a mixed gas of chlorine, oxygen and helium; S60, performing vitrification, sintering and drawing treatments on the dried reaction tube to obtain a thulium-doped optical fiber.
[0008] Preferably, in step S10, the flow rate of sulfur hexafluoride in the first mixed gas is greater than 0 and less than or equal to 50 sccm, and the flow rate of silicon tetrachloride is greater than 100 sccm and less than 300 sccm.
[0009] Preferably, step S10 further includes: using an oxyhydrogen lamp to bake the first reaction tube at a baking temperature of 1400-2100° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas in the first reaction tube.
[0010] Preferably, in step S20, the flow rate of silicon tetrachloride in the second mixed gas is greater than 150 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 150 sccm and less than or equal to 300 sccm.
[0011] Preferably, step S20 further includes: using an oxyhydrogen lamp to bake the second reaction tube at a baking temperature of 1400-2100° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the second reaction tube.
[0012] Preferably, in step S30, the flow rate of silicon tetrachloride in the third mixed gas is greater than 180 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 100 sccm and less than or equal to 200 sccm.
[0013] Preferably, step S30 further includes: using an oxyhydrogen lamp to bake the third reaction tube at a baking temperature of 800-1400° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the third mixed gas in the third reaction tube.
[0014] Preferably, in step S40, the soaking time is 0.5 to 2 hours, the solvent of the ion solution is deionized water or anhydrous ethanol, and the solute includes at least Tm 3+ and Al 3+ , Tm in the first ion solution 3+ The concentration is 0.03~0.2mol / l, Al 3+ The concentration is 0.03~0.2mol / l.
[0015] Preferably, in step S50, the immersed third reaction tube is baked using an oxyhydrogen lamp at a baking temperature of 800-1300° C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the fourth mixed gas in the third reaction tube.
[0016] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention provides a thulium-doped optical fiber and a preparation method thereof, wherein the core layer of the thulium-doped optical fiber comprises a germanium-aluminum-thulium co-doped silicate material, the presence of germanium in the core layer can reduce the phonon energy of the core layer, and a certain amount of aluminum ions co-doped in the core layer can disperse the distance between thulium ions, thereby greatly improving the cross-relaxation probability between thulium ions in the core layer, and ultimately improving the optical fiber efficiency of the thulium-doped optical fiber; further, a transition step layer of germanium-silicate material is arranged on the periphery of the core layer, which can reduce the relative refractive index of the core layer, thereby reducing the numerical aperture of the core layer, which is beneficial to the single-mode output of the laser. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A flow chart of a method for preparing a thulium-doped optical fiber provided in an embodiment of the present invention; Figure 2 EPMA line scan of the thulium-doped optical fiber provided in Example 1 of the present invention; Figure 3 EPMA line scan of the thulium-doped optical fiber provided in Comparative Example 1; Figure 4 This is a comparison chart of the slope efficiency of the thulium-doped optical fiber provided in Example 1 of the present invention and the thulium-doped optical fiber provided in Comparative Example 1. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] In view of the technical problem of low optical fiber efficiency of thulium-doped optical fibers in the prior art, the present invention proposes a high-efficiency thulium-doped optical fiber and a preparation method thereof; the present invention prepares a highly doped and high-efficiency thulium-doped optical fiber by combining MCVD (Modified Chemical Vapor Deposition) with a solution doping method, and the prepared thulium-doped optical fiber has the advantages of high doping, high efficiency, high beam quality, etc.
[0020] In a first aspect, the present invention first provides a thulium-doped optical fiber, comprising a core layer, a transition step layer, a barrier layer, a cladding layer and a coating layer arranged in sequence from the inside to the outside along a radial direction, wherein the refractive index of the transition step layer is greater than the refractive index of the cladding layer and less than the refractive index of the core layer; The core layer comprises germanium-aluminum-thulium co-doped silicate material, the transition step layer comprises germanium silicate material, and the barrier layer comprises fluorosilicate material.
[0021] Specifically, the core layer of the above-mentioned thulium-doped optical fiber includes a germanium-aluminum-thulium co-doped silicate material. The presence of germanium in the core layer can reduce the phonon energy of the core layer, and a certain amount of aluminum ions co-doped in the core layer can disperse the distance between thulium ions, thereby greatly increasing the cross-relaxation probability between thulium ions in the core layer, thereby ultimately improving the optical fiber efficiency of the thulium-doped optical fiber.
[0022] Specifically, a transition step layer of germanosilicate material is arranged outside the core layer, and the refractive index of the transition step layer is greater than the refractive index of the cladding layer and less than the refractive index of the core layer; the above design can reduce the relative refractive index of the core layer, thereby reducing the numerical aperture of the core layer, which is beneficial to the single-mode output of the laser.
[0023] Specifically, the barrier layer includes a fluorosilicate material. The barrier layer is provided to prevent hydroxyl groups generated by the hydrogen-oxygen flame of an hydrogen-oxygen lamp used in the subsequent preparation process from diffusing into the core layer, because the loss of thulium laser by hydroxyl groups is very large.
[0024] See also Figure 1 , Figure 1 A flow chart of a method for preparing a thulium-doped optical fiber provided in an embodiment of the present invention; the method for preparing the thulium-doped optical fiber comprises the following steps: S10, introducing a first mixed gas into a quartz tube to deposit a barrier layer on the inner wall of the quartz tube to obtain a first reaction tube, wherein the first mixed gas includes a mixed gas of oxygen, silicon tetrachloride and sulfur hexafluoride.
[0025] Specifically, step S10 also includes: A clean reaction tube is placed on a lathe, and a first mixed gas is introduced into a quartz tube (a high-purity quartz reaction tube, model F300 of Heraeus) and a barrier layer containing fluorine ions is deposited on the inner wall of the quartz tube to obtain a first reaction tube; the first mixed gas includes a mixed gas of oxygen, silicon tetrachloride and sulfur hexafluoride; at this time, the obtained barrier layer is a fluorine-containing silicate material.
[0026] Specifically, in step S10, the flow rate of sulfur hexafluoride in the first mixed gas is greater than 0 and less than or equal to 50 sccm, and the flow rate of silicon tetrachloride is greater than 100 sccm and less than 300 sccm; this indicates that the amount of sulfur hexafluoride added is relatively small, but its role may be crucial to forming specific barrier layer properties. The flow rate of silicon tetrachloride is greater than 100 sccm and less than 300 sccm. Silicon tetrachloride is one of the main raw materials for forming the deposited layer, and the setting of its flow range affects the thickness and quality of the deposited layer.
[0027] Specifically, step S10 also includes: while introducing the first mixed gas, using a hydrogen-oxygen lamp to bake the first reaction tube, the baking temperature is 1400-2100°C, and the moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the first mixed gas in the first reaction tube; wherein, this baking treatment helps to improve the quality and performance of the barrier layer, such as enhancing its adhesion and improving crystallinity. The setting that the moving direction of the hydrogen-oxygen lamp is the same as the gas flow direction helps to achieve a more uniform heating effect, thereby ensuring the consistency and stability of the barrier layer.
[0028] S20, introducing a second mixed gas into the first reaction tube to deposit a transition step layer on the inner wall of the first reaction tube to obtain a second reaction tube, wherein the second mixed gas includes a mixed gas of oxygen, silicon tetrachloride and germanium tetrachloride.
[0029] Specifically, step S20 also includes: After the barrier layer is deposited, a second mixed gas is introduced into the first reaction tube to deposit a circle of transition step layer containing Ge to obtain a second reaction tube. The second mixed gas includes a mixed gas of oxygen, silicon tetrachloride and germanium tetrachloride. At this time, the obtained transition step layer is a germanosilicate material.
[0030] Specifically, in step S20, the flow rate of silicon tetrachloride in the second mixed gas is greater than 150 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 150 sccm and less than or equal to 300 sccm.
[0031] Specifically, step S20 also includes: using a hydrogen-oxygen lamp to bake the second reaction tube, the baking temperature is 1400-2100° C., and the moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the second mixed gas in the second reaction tube.
[0032] S30, introducing a third mixed gas into the second reaction tube to deposit a loose layer on the inner wall of the second reaction tube to obtain a third reaction tube, wherein the third mixed gas includes a mixed gas of oxygen, helium, silicon tetrachloride and germanium tetrachloride.
[0033] Specifically, step S30 also includes: A third mixed gas is introduced into the second reaction tube where the transition step layer is deposited, and a loose layer is deposited on the inner wall of the second reaction tube to obtain a third reaction tube. The third mixed gas includes a mixed gas of oxygen, helium, silicon tetrachloride and germanium tetrachloride; the obtained loose layer is a germanosilicate material.
[0034] Specifically, the purpose of the loose layer of germanosilicate material is mainly to make the subsequent Tm 3+ and Al 3+ It is incorporated into the quartz reaction tube through the pores of the loose layer.
[0035] Furthermore, in step S30, the flow rate of silicon tetrachloride in the third mixed gas is greater than 180 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 100 sccm and less than or equal to 200 sccm.
[0036] Specifically, step S30 also includes: using a hydrogen-oxygen lamp to bake the third reaction tube at a baking temperature of 800-1400° C., and the moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the third mixed gas in the third reaction tube.
[0037] Furthermore, the reason why the baking temperature in step S30 is lower than the baking temperature in step S10 or step S20 is as follows: High temperature may cause unnecessary over-reaction of the components in the third mixed gas, affecting the composition and properties of the loose layer. Lower temperature helps to control the progress of the reaction, so that it can form the desired loose layer more accurately. Lower baking temperature can reduce the impact on the formed structure of the barrier layer and transition step layer, preventing them from changing performance or structural damage at high temperature.
[0038] S40, immerse the third reaction tube in a solution containing Tm 3+ and Al 3+ in ionic solution.
[0039] Specifically, step S40 also includes: The third reaction tube with a loose layer on the inner wall is immersed in a Tm 3+ and Al 3+ In ionic solution, Tm 3+ and Al 3+doped into the germanosilicate material through the pores of the loose layer; the immersion time is 0.5 to 2 hours, the solvent of the ion solution is deionized water or anhydrous ethanol, and the solute includes at least Tm 3+ and Al 3+ , Tm in the first ion solution 3+ The concentration is 0.03~0.2mol / l, Al 3+ The concentration is 0.03~0.2mol / l.
[0040] S50, baking the third reaction tube under a fourth mixed gas to obtain a dry reaction tube, the fourth mixed gas comprising a mixed gas of chlorine, oxygen and helium.
[0041] Specifically, step S50 also includes: While the fourth mixed gas is introduced into the third reaction tube, the third reaction tube after immersion is baked using a hydrogen-oxygen lamp at a baking temperature of 800-1300° C. The moving direction of the hydrogen-oxygen lamp is the same as the flow direction of the fourth mixed gas in the third reaction tube; this can make the loose layer condense quickly, which is beneficial to Tm 3+ and Al 3+ Fixed in the loose layer.
[0042] S60, performing vitrification, sintering and drawing treatments on the dried reaction tube to obtain a thulium-doped optical fiber.
[0043] Specifically, step S60 further includes: S601, introducing oxygen into the dry reaction tube to vitrify the inner wall of the dry reaction tube, and then sintering to form a transparent quartz preform; S602, inserting the quartz preform rod into the sleeve, and drawing it into an optical fiber in a drawing tower, namely, thulium-doped optical fiber.
[0044] Preferably, in step S601, the temperature for vitrification of the dry reaction tube is 1900-2300° C., and the pressure inside the dry reaction tube during vitrification is 0.6-0.9 Torr; the temperature for shrinking the dry reaction tube is 2000-2200° C., and the pressure inside the dry reaction tube during shrinking is 0.1-0.3 Torr.
[0045] In summary, the preparation method of thulium-doped optical fiber provided by the present invention first introduces Ge element into the core layer, reduces the phonon energy of the core layer, and greatly improves the cross-relaxation probability between thulium ions in the core layer; then, a circle of Ge steps is prepared around the core layer to reduce the numerical aperture of the core layer, which is beneficial to the single-mode output of the laser; then, the quartz reaction tube containing the loose layer is immersed in a Tm-containing 3+ The ionic solution of 3+The mixture is doped into the third reaction tube through the pores of the loose layer of SiO2 material; the third reaction tube is then baked to reduce Tm 3+ The fiber is fixed in a dry quartz tube; finally, the dry quartz tube is subjected to a vitrification, sintering and drawing process to obtain a high-efficiency thulium-doped optical fiber; the present invention optimizes the core components and greatly improves the cross-relaxation probability of thulium ions in the thulium-doped optical fiber without changing or upgrading the existing MCVD conventional preparation conditions. The method is extremely suitable for the existing preparation process system.
[0046] The technical solution of the present application is now described in conjunction with specific embodiments.
[0047] Embodiment 1: Embodiment 1 of the present invention first provides a thulium-doped optical fiber, comprising a core layer, a transition step layer, a barrier layer, a cladding layer and a coating layer arranged in sequence from the inside to the outside along the radial direction, wherein the refractive index of the transition step layer is greater than the refractive index of the cladding layer and less than the refractive index of the core layer; The core layer comprises germanium-aluminum-thulium co-doped silicate material, the transition step layer comprises germanium silicate material, and the barrier layer comprises fluorosilicate material.
[0048] Accordingly, Embodiment 1 of the present invention further provides a method for preparing a thulium-doped optical fiber, which comprises the following steps: Step 1, depositing a barrier layer of fluorosilicate material on the inner wall of a reaction tube made of quartz material; Step 2, depositing a transition step layer of germanosilicate material on the barrier layer; Step 3, depositing a loose layer of germanosilicate material on the basis of the reaction tube with the transition step layer; Step 4: Soak the reaction tube with the loose layer in water containing TM 3+ and Al 3+ In water or ethanol solution of ions, Tm 3+ The ion concentration is 0.1 mol / L, Al 3+ The ion concentration is 0.1 mol / L; Step 5: Place the soaked reaction tube in nitrogen and purge it to remove large water droplets in the tube. The nitrogen flow rate is 30 sccm and the purge time is 4 hours. Step 6, placing the quartz reaction tube obtained in step 5 on a hydrogen-oxygen lamp for high-temperature baking, while introducing a certain amount of mixed gas containing silicon tetrachloride, oxygen, helium, nitrogen and chlorine into the tube, while maintaining the pressure in the reaction tube sufficiently high, the baking temperature is 1200-1400° C., and the chlorine flow rate is 150 sccm; Step 7: Then, the temperature is raised to vitrify the inner wall of the quartz reaction tube, so that the loose layer on the tube wall condenses quickly, locking the TM in the pores. 3+ Ions and Al 3+ions, the glass transition temperature is 2200°C, and the pressure in the tube is maintained at 0.6 Torr; Step eight, sintering the reaction tube obtained in step seven at 2000-2200° C. into a transparent quartz preform rod; Step nine, inserting the quartz preform rod into a sleeve of suitable size, and drawing it into an optical fiber in a drawing tower.
[0049] Comparative Example 1: Comparative Example 1 provides a thulium-doped optical fiber and a preparation method thereof. The other steps of the preparation method of the thulium-doped optical fiber provided in Comparative Example 1 are the same as those in Example 1, except that the loose layer deposited in step three is a silicate matrix material, the phonon energy of the matrix material is greater than that of the germanosilicate matrix material, and the cross-relaxation probability is significantly lower than that in Example 1.
[0050] See also Figure 2 as well as Figure 3 , Figure 2 This is an EPMA (Electron Probe Microanalysis) line scan of the thulium-doped optical fiber provided in Example 1 of the present invention. Figure 3 The EPMA line scan diagram of the thulium-doped optical fiber provided in Comparative Example 1, the horizontal axis is the distance (μm) along a selected straight line direction of the sample surface, and the vertical axis is the molar distribution (mol) of the element in the core; wherein the optical fiber preforms prepared in Example 1 and Comparative Example 1 are sampled by optical fiber drawing of the same optical fiber model, and the core components are tested by electron probe microscopy, and the results are as follows Figure 2 as well as Figure 3 As shown in the comparative example 1, since the loose layer added in step 3 is a silicate matrix and no germanium element is added, Figure 3 The core layer of the fiber does not show any distribution of germanium.
[0051] Since it is impossible to directly observe whether cross-relaxation occurs between thulium ions, it is necessary to observe it indirectly through the slope efficiency of the optical fiber; under the same thulium ion loading, the higher the slope efficiency, the higher the probability of cross-relaxation.
[0052] See also Figure 4 , Figure 4 The slope efficiency comparison diagram of the thulium-doped optical fiber provided in Example 1 of the present invention and the thulium-doped optical fiber provided in Comparative Example 1 is shown in FIG. Figure 4 It can be seen that in Comparative Example 1, since the loose layer doped in step 3 is a silicate matrix without germanium doped, the probability of cross relaxation occurring in this matrix is much lower than that in Example 1, and the slope efficiency is significantly lower than that in Example 1.
[0053] In order to prepare thulium-doped optical fiber with high optical fiber efficiency, the present invention adopts the following two measures: First, increase the content of Ge in the core components: The key to high fiber efficiency of thulium-doped fiber is to increase the cross-relaxation probability between thulium ions in the fiber. For thulium-doped fiber, if the most commonly used 793 commercial pump source is used to pump thulium ions to emit light near the 2μm band, its light-to-light conversion efficiency is only 40%, but the unique cross-relaxation mechanism of thulium ions makes its quantum efficiency as high as 200%, and the light-to-light conversion efficiency can be directly doubled to 80% in theory. Therefore, how to increase the cross-relaxation probability between thulium ions is crucial.
[0054] The conventional silicate matrix glass we currently use has a relatively high phonon energy (1100 cm -1 ), which will lead to rapid multi-phonon relaxation, thus reducing the luminescence performance and quantum efficiency, so it is not an ideal carrier for 2μm lasers. Therefore, the quantum efficiency and output power of silicate-based thulium-doped fibers are quite limited. In contrast, germanosilicate-based glass provides relatively low phonon energy (950cm -1 ), so it can provide more cross-relaxation probability, and its infrared transmittance is much better than that of pure silicate matrix fiber. When preparing optical fiber preform, adding a certain amount of Ge element to the active area of the optical fiber can improve the efficiency of thulium-doped optical fiber.
[0055] At the same time, it will be mentioned below that a transition step layer of germanosilicate material is doped around the core layer. A certain amount of Ge element is doped into the core layer, which can also reduce the stress between the core layer and the surrounding transition step layer, and reduce the probability of the optical fiber preform being scrapped due to excessive stress during the preparation of the optical fiber preform.
[0056] Second, Ge is doped around the core layer: In addition, since the cross relaxation of thulium ions has certain requirements on the load of thulium ions, and also has certain requirements on the distance between thulium ions, it is necessary to co-dope a certain amount of Al elements to disperse the distance between thulium ions. Therefore, high thulium and high Al elements provide a very high core refractive index to the core part, which makes the numerical aperture of thulium-doped optical fiber very high, making it difficult to adapt to conventional passive devices on the market. It is necessary to make a transition step layer of germanium silicate material around the core to reduce the relative refractive index of the core layer to adapt to passive devices. In addition, low NA (Numerical Aperture) is more conducive to single-mode laser output.
[0057] Compared with the prior art, the high fiber efficiency thulium-doped optical fiber provided by the present invention has the following advantages: First, when the loose layer of the active region of the thulium-doped optical fiber with high optical fiber efficiency provided by the present invention is deposited, the matrix material of the active region is a germanosilicate matrix, which not only has a lower phonon energy, which is conducive to the occurrence of cross relaxation, but also has better mid-infrared laser transmittance, reducing transmission loss; Second, the high fiber efficiency thulium-doped optical fiber provided by the present invention has a transition step layer of germanosilicate material deposited around the core layer. This transition step layer can reduce the numerical aperture of the core layer, ensure the laser is output in single mode, and better match the active devices on the market.
[0058] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0059] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A thulium-doped optical fiber, characterized in that: It comprises a core layer, a transition step layer, a barrier layer, a cladding layer and a coating layer which are arranged in sequence from the inside to the outside along the radial direction, wherein the refractive index of the transition step layer is greater than the refractive index of the cladding layer and less than the refractive index of the core layer; The core layer comprises germanium-aluminum-thulium co-doped silicate material, the transition step layer comprises germanium silicate material, and the barrier layer comprises fluorosilicate material.
2. A method for preparing a thulium-doped optical fiber as claimed in claim 1, characterized in that: The method comprises: S10, introducing a first mixed gas into a quartz tube to deposit a barrier layer on the inner wall of the quartz tube to obtain a first reaction tube, wherein the first mixed gas includes a mixed gas of oxygen, silicon tetrachloride and sulfur hexafluoride; S20, introducing a second mixed gas into the first reaction tube to deposit a circle of the transition step layer on the inner wall of the first reaction tube to obtain a second reaction tube, wherein the second mixed gas includes a mixed gas of oxygen, silicon tetrachloride and germanium tetrachloride; S30, introducing a third mixed gas into the second reaction tube to deposit a loose layer on the inner wall of the second reaction tube to obtain a third reaction tube, wherein the third mixed gas includes a mixed gas of oxygen, helium, silicon tetrachloride and germanium tetrachloride; S40, immersing the third reaction tube in a solution containing Tm 3+ and Al 3+ in ionic solution; S50, baking the third reaction tube under a fourth mixed gas to obtain a dry reaction tube, wherein the fourth mixed gas includes a mixed gas of chlorine, oxygen and helium; S60, performing a vitrification, sintering and drawing process on the dried reaction tube to obtain the thulium-doped optical fiber.
3. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: In the step S10, the flow rate of sulfur hexafluoride in the first mixed gas is greater than 0 and less than or equal to 50 sccm, and the flow rate of silicon tetrachloride is greater than 100 sccm and less than 300 sccm.
4. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: The step S10 further includes: using an oxyhydrogen lamp to bake the first reaction tube at a baking temperature of 1400-2100° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the first mixed gas in the first reaction tube.
5. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: In the step S20, the flow rate of silicon tetrachloride in the second mixed gas is greater than 150 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 150 sccm and less than or equal to 300 sccm.
6. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: The step S20 further includes: using an oxyhydrogen lamp to bake the second reaction tube at a baking temperature of 1400-2100° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the second mixed gas in the second reaction tube.
7. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: In the step S30, the flow rate of silicon tetrachloride in the third mixed gas is greater than 180 sccm and less than or equal to 300 sccm, and the flow rate of germanium tetrachloride is greater than 100 sccm and less than or equal to 200 sccm.
8. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: The step S30 further includes: using an oxyhydrogen lamp to bake the third reaction tube at a baking temperature of 800-1400° C., and the moving direction of the oxyhydrogen lamp is the same as the flow direction of the third mixed gas in the third reaction tube.
9. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: In the step S40, the soaking time is 0.5 to 2 hours, the solvent of the ion solution is deionized water or anhydrous ethanol, and the solute includes at least Tm 3+ and Al 3+ , the first ion solution Tm 3+ The concentration is 0.03~0.2mol / L, Al 3+ The concentration is 0.03~0.2mol / L.
10. The method for preparing thulium-doped optical fiber according to claim 2, characterized in that: In the step S50, the immersed third reaction tube is baked using an oxyhydrogen lamp at a baking temperature of 800-1300° C. The moving direction of the oxyhydrogen lamp is the same as the flow direction of the fourth mixed gas in the third reaction tube.
Citation Information
Patent Citations
Three-wrapping-layer thulium-doped optical fiber and preparation method thereof
CN104932054A
High-power, single-mode fiber sources
CN105826798A
Alkali metal doped optical fiber and preparation method thereof
CN114075037A
Thulium and / or Holmium Doped Germanosilicate Glasses for Two Micron Lasers
US20120269210A1